Enhancing critical thinking skills through GeoGebra-based learning media in geometry transformation lessons for grade 11 students - Adiguna, Kukuh Arya; Sunardi, Sunardi; Prastiti, Tri Dyah (Mahesa Research Center, 2025)
This study aims to develop and test the effectiveness of GeoGebra-based mathematics learning media on the critical thinking skills of 11th-grade high school students in the topic of geometric transformations. The research employed the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. During the analysis stage, interviews and pre-tests were conducted to identify students' needs and assess their initial abilities. The design stage involved creating GeoGebra-based learning media, developing assessment instruments, and designing lesson plans (RPP) using the PMRI model. In the development stage, the learning media were validated by media and content experts and tested on students of class XI MIPA 3 at SMA Negeri 1 Bangorejo. The implementation stage consisted of two sessions for teaching and testing. The evaluation stage included analyzing pre-test and post-test results using N-gain tests, normality tests, homogeneity tests, and paired sample t-tests. The results showed that the GeoGebra-based learning media achieved an excellent level of validity, with media validity at 95% and content validity at 85%. Furthermore, the media were rated as highly practical by students, with an average questionnaire score of 85%. The N-gain test indicated a